Bayesian Analysis of Multivariate Threshold Autoregressive Models with Missing Data (2014)
In some fields, we are forced to work with missing data in multivariate time series, unfortunately the analysis in this context cannot be done as in the case of complete data. Bayesian analysis of multivariate thresholds autoregressive models(MTAR) with exogenous inputs and missing data is carried out. MCMC methods are used to obtain samples from the marginal posterior distributions, including threshold values and missing data. In order to identify autoregressive orders, we adapt the Bayesian variable selection method to the MTAR models. The number of regimes is estimated using marginal likelihood and product space strategies. The forecasting of the output vector is implemented finding its predictive distributions. Simulation experiments and real data examples are presented.